Volume 2: Controls, Diagnostics and Instrumentation; Cycle Innovations; Electric Power 2008
DOI: 10.1115/gt2008-51357
|View full text |Cite
|
Sign up to set email alerts
|

Combined-Cycle Power Plant Maintenance Costs

Abstract: This paper describes a methodology to quantify scheduled and unscheduled maintenance costs and a software framework for estimating operations and maintenance (O&M) costs of combined-cycle power plants over their operating life. Scheduled maintenance costs consist primarily of replacement and repair of hot section components of the combustion turbine that occur during planned inspections and overhaul events. Scheduled maintenance costs can be estimated based on anticipated parts life, operating conditions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…At a minimum, cost of failure is the sum total of cost of repairs (parts, materials, and labor) and downtime (lost opportunity of power generation) and can be much higher in certain cases such as major accidents [13,14]. Its exact value is not that important from a conceptual analysis perspective (of the order of $5000/MW-yr for E and F-class plants based on the study in Ref.…”
Section: (7)mentioning
confidence: 99%
See 1 more Smart Citation
“…At a minimum, cost of failure is the sum total of cost of repairs (parts, materials, and labor) and downtime (lost opportunity of power generation) and can be much higher in certain cases such as major accidents [13,14]. Its exact value is not that important from a conceptual analysis perspective (of the order of $5000/MW-yr for E and F-class plants based on the study in Ref.…”
Section: (7)mentioning
confidence: 99%
“…Also in Eq. (13), Ph is the annual load and ambient-weighted average unit output to be used as a basis in COE comparison. For multiple unit comparisons, it can be set to the highest P among the alternatives.…”
Section: System Considerationsmentioning
confidence: 99%
“…The authors clarify that to reduce the operating costs, the engines are demanded to operate longer and reduce maintenance costs. For instance, the costs of maintenance for gas fired combined cycle plants can reach 50% of the total O&M costs [3] and represent 7% of the overall project cash flow. Additionally, statistic studies conducted over 3000 E and F class engines concluded that the unplanned maintenance cost can reach 8% of the O&M costs, or 2% of net revenue income and the loss of revenue can reach the 15% of the O&M cost or 5% of net revenue income [4].…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial work reported in 2001 and refinements presented in 2008 [2], the statistical basis and costing methodology have been expanded. Furthermore, significantly more experience has been gained from the operation of F-Class gas turbines, particularly as it relates to unplanned maintenance events.…”
Section: Introductionmentioning
confidence: 99%